Translation Techniques and Appropriateness of English Idioms in The Founder - Nadeline Calista Modesty; Ivonne Muliawati Harsono (Institute of Research and Community Outreach - Petra Christian University, 2023)
This thesis is about the idiom translation of the movie The Founder by John Lee Hancock. In this thesis, the writer analyzes the techniques and appropriateness of the idiom translation by using Molina and Albir (2002) and Larson's accuracy, clarity, and naturalness (1984) theory. The writer seeks to disclose the most common technique used for translating idioms and how to make a good-quality translation. This study was done using a qualitative approach. The data analysis showed that out of 18 techniques proposed by Molina and Albir (2002) only 5 were utilized by the translator and out of five techniques, the established equivalent was used the most. The data analysis also shows that among 20 idioms, 10 idioms are appropriately translated. The writer suggests that future studies could be conducted on other aspects of the subtitles of The Founder.